Contemporary sport management - Thibault, Lucie PhD; Pedersen, Paul M. PhD 1970- (Human Kinetics, Inc., 2022)
Short, factual description of the book (summary of what it includes, without subjective or promotional language.) This classic but thoroughly updated introductory text is designed so students will understand sport management as a field of study and a vibrant professional environment. It emphasizes critical-thinking, ethics, and diversity while providing a broad introduction to the major functional areas and issues that student will encounter in their careers